ACADEMIC NEW FRONTIERS: cooperation between research groups in Information Science in Brazil - Freire, Isa Maria; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP] (Univ Federal Campina Grande, 2012)
Displays the context of the Project Network cooperation and learning in information science: PPGCI/UFPB and PPGCI/UNESP/Marilia, under the National Program of Academic Cooperation - Action New Frontiers (NF-Procad) Coordination for the Improvement of Higher (CAPES). Describes the procedures for financing, consisting of Missions Studies, Missions Teaching and Research and Post-Doctoral Internship in the country highlights the Groups and Research areas involved in the project and discusses the theoretical approach adopted and the conceptual network that guides actions teaching and research. We report the activities in the first two years of the project and discusses ongoing and planned activities.
Keywords: Academic Cooperation; Capes - Program of Academic Cooperation; Information Science - Graduate; UFPB; UNESP/Marilia